2012
DOI: 10.1002/cbm.1832
|View full text |Cite
|
Sign up to set email alerts
|

Investigating changes in anger and aggression in offenders with high levels of psychopathic traits attending the Chromis violence reduction programme

Abstract: Findings support the continued delivery and evaluation of Chromis. There may be benefit in exploring ways to further understand and address verbal aggression in participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 13 publications
1
27
2
2
Order By: Relevance
“…Contrary to our initial hypothesis, and findings from previous evaluations of offenders who had experienced the PD treatment programme at this prison (Tew et al, 2012; Bennett and Moss 2013), our study found a statistically significant increase in frequency of SH and PRB behaviours engaged in by 74 men from the living to treatment phase of the PD treatment programme.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Contrary to our initial hypothesis, and findings from previous evaluations of offenders who had experienced the PD treatment programme at this prison (Tew et al, 2012; Bennett and Moss 2013), our study found a statistically significant increase in frequency of SH and PRB behaviours engaged in by 74 men from the living to treatment phase of the PD treatment programme.…”
Section: Discussioncontrasting
confidence: 99%
“…The restrictive nature of prison, maintain professional boundaries between staff and prisoner, and insincere behaviour by some men, have limited the access to these support services and may impact on the level of distress experienced by men with PD when they are experiencing crisis (Bennett, 2014). (Tew et al, 2012). These studies demonstrate tentative progress for offenders.…”
Section: Dsm V Personality Disorder Clusters and Subtypesmentioning
confidence: 66%
See 3 more Smart Citations